Modulating Reaction Kinetics Using an Electrolytic Method to Achieve Efficient Vehicle Identification Number Reappearance - Jintao Wang; Xiaoshun Zhang; Mengfan Chen; Xihao Zhang; Zhongliang Zhang; Jianguo Liu (Micromachines)
Vehicle identification number (VIN) reappearance technology is an important means of vehicle traceability in various criminal cases. However, with the advancement of metallurgical techniques, the corrosion resistance of metal becomes stronger, and the traditional chemical etching reappearance method gradually fails. In order to break through the dilemma of traditional methods, this study establishes an electrochemical corrosion system by introducing the corrosion inhibitor hexamethylenetetramine (HMTA) to precisely regulate the electrochemical dissolution kinetics. Material characterization and electrochemical measurements demonstrated that the selective adsorption of HMTA significantly enhances the potential difference between plastically deformed regions and the normal metal substrate (ΔEmax = 6 mV). By effectively suppressing the corrosion rate in non-target areas, HMTA promotes selective anodic oxidation reactions in the vehicle identification number character regions due to their distinct microstructural characteristics, thereby substantially improving the contrast of the reappeared VIN markings. Density functional theory calculations and molecular dynamics simulations further reveal the formation of a dense adsorption layer, which is a key factor in improving the reproducibility of the results. The experimental results demonstrate that under conditions of 6 V applied voltage, with 0.5 M hydrochloric acid and 0.02–0.03 M HMTA in the electrolyte, efficient VIN reappearance could be achieved within 3–4 min on filed-down surfaces.